Trabalho em plataformas digitais: os direitos fundamentais dos trabalhadores face às novas formas de subordinação e aos preceitos do trabalho digno e do trabalho decente - Barreto, Clessine Cuzzol Nunes (2022)
This dissertation proposes the study of the worker on digital platforms reality, in the context of the 4.0 Revolution. Considered independents, they are completely removed from all the labor rights of the formal jobs. Starting from the study of the fundamental rights of workers, it is questioned: given the changes around the subordination that characterize work on digital platforms, in which way can the precepts of dignified work and decent work be met? The objectives of the research are: to study the organization of work since the industrial revolutions till the new forms of work of the fourth industrial revolution, the gig economy, the work on digital platforms and analyse the reality of these workers; to investigate the legal nature of the relationship between workers and digital platforms, especially regarding the new forms of algorithmic subordination, comparing the national jurisprudence and labor legislation with the foreigners jurisprudence and legislation; to discuss about the fundamental rights of workers, from the perspective of the right of dignified work and decent work and its application on work on digital platforms. The research is divided in three chapters, according to the objectives presented. It is adopted the dialectical method to comprehend the evolution of capitalism and the work relationships in the context of the digital revolution, developing the research through bibliographic and documentary research, which the sources are the doctrine, legal norms and court decisions. Finally, it is concluded that although the Brazilian legislation and jurisprudence are in an inaugural phase of recognition of workers' rights on digital platforms, the adoption of the concepts of dignified work and decent work must be considered for the realization of the fundamental rights of these workers.